A First Look at PCMH Implementation for Minority Veterans: Room for Improvement. Issue 3 (March 2016) - Hernandez, Susan E.; Taylor, Leslie; Grembowski, David; Reid, Robert J.; Wong, Edwin; Nelson, Karin M.; Liu, Chuan-Fen; Fihn, Stephan D.; Hebert, Paul L.
Abstract : Background: Implementation of Patient Aligned Care Teams (PACT), a patient-centered medical home model, has been inconsistent among the >900 primary care facilities in the Veterans Health Administration. Objective: Estimate if the degree of PACT implementation at a facility varied with the percentage of minority veteran patients at the facility. Research Design: Cross-sectional, facility-level analysis of PACT implementation measures in 2012. Subjects: Veterans Health Administration hospital-based and community-based primary care facilities. Measures: We used a previously validated PACT Implementation Progress Index (Pi 2 ) and its 8 domains: access, continuity of care, care coordination, comprehensiveness, self-management support, and patient-centered care and communication, shared decision-making domains, and team functioning. Facilities were categorized as low (<5.2%, n=208), medium (5.2%–25.8%, n=413), and high (>25.8%, n=206) percent minority based on the percent of their own veteran population. Results: Most minority veterans received care in high minority (69%) and medium minority facilities (29%). In adjusted analyses, medium and high minority facilities scored 0.773 ( P =0.009) and 0.930 ( P =0.008) points lower on the Pi 2 score relative to low minority facilities. Relative to low minority facilities, both medium and high minority facilities were less likely of having high Pi 2 scores (≥2) and more likely of having low Pi 2 scores (⩽−2). Both medium and high minority facilities had the same 3 domain scores lower than low minority facilities (care coordination, comprehensiveness, and self-management). Conclusion: Overall PACT implementation varied with respect to the racial/ethnic composition of a facility, with medium and high minority facilities having a lower implementation scores. Abstract : Supplemental Digital Content is available in the text.